Comprehension of Traffic Signs among Aeta Motorists: From Challenges to Solutions - Inong, Clariza Buay (Future Science / FSH-PH Publications, 2025)
Traffic signs are vital for ensuring motorists safety on the road, but their effectiveness relies on drivers comprehending their meaning and demonstrating the appropriate actions. This study investigated the traffic sign comprehension of 324 Aeta respondents using a three-part questionnaire: a survey on respondents’ agreement with traffic sign meanings and actions, a matching test to identify traffic sign names, both using convenience sampling, and an interview us-ing purposive sampling. The researcher utilized a convergent paral-lel mixed method design, examining quantitative data with descrip-tive statistics and qualitative data with thematic analysis. The key findings indicate that the overall traffic sign comprehension mean score of the respondents was 3.35, interpreted as “Average,” sug-gesting a general understanding of traffic signs with room for im-provement in specific areas. The data also reveals that the most cor-rectly identified signs in the matching test were those reinforced with both verbal and non-verbal elements and those frequently en-countered, such as the informative sign “Slow Vehicles Use Right Lane” (49.4 %), the warning sign “Slippery When Wet” (47.8%), the regulatory sign “Stop Sign” (66.0%) and the road marking “Single Solid Yellow Line” (46.6%). Most Aeta motorists began driving at a young age without formal training, mostly learning through obser-vations and guidance from family and relatives, leading to misun-derstandings of traffic signs. Interviews highlighted that financial difficulties, lack of resources, and illiteracy prevent many Aeta mo-torists from obtaining driver’s licenses and vehicle registrations. Additionally, they often face prejudice and discrimination, being unfairly blamed for motor vehicle accidents. These findings empha-size the importance of specialized educational initiatives and cul-turally appropriate driving instruction to promote traffic sign litera-cy among Aeta motorists. Proposed initiatives include the develop-ment of simple, engaging materials, such as a tri-fold brochure con-taining locally translated traffic sign names, explanations of Kapampangan language, and pictures. Other rec-ommendations include free or subsidized driver education courses and improved traffic signs combining verbal and non-verbal ele-ments to enhance comprehension.